Planeamiento de la expansión de sistemas de transmisión considerando contingencias y demanda incierta - Gallego Pareja, Luis Alfonso [UNESP]; Romero, Rubén Augusto [UNESP]; López Lezama, Jesús María (My University, 2009)
This paper presents a methodology and a mathematical model to solve the expansion planning problem that takes into account the effect of contingencies in the planning stage, and considers the demand as a stochastic variable within a specified range. In this way, it is possible to find a solution that minimizes the investment costs guarantying reliability and minimizing future load shedding. The mathematical model of the expansion planning can be represented by a mixed integer nonlinear programming problem. To solve this problem a specialized Genetic Algorithm combined with Linear Programming was implemented.
Transmission network expansion planning considering contingencies and uncertain demand
Keywords: Genetic algorithms; Power system reliability; Transmission planning; Uncertain demand